On Recognizability of the Group E_8(q) by the Set of Orders of Elements - Alekseeva, O. A.; Kondratiev, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We prove that if a finite group G has the same set of orders of elements as the group E 8(q), then O 3(G/F(G)) is isomorphic to E 8(q).